When less is better than more: Just-below discount in tensile price promotions. (July 2016) - Banerjee, Prantosh J.; Tripathi, Sanjeev; Sahay, Arvind
Abstract: Retailers often use Tensile Price Claims (TPC) such as "upto 40% off" or "from 10% to 40% off" to promote a line of merchandize. This enables them to have a salient communication while allowing specific level of discount on particular items. Recently, retailers have started using just-below TPC frames such as "upto 39% off". This research explores the influence of TPC framed with "just-below" numbers on consumers' perceived benefits through three studies. The results indicate that just-below temporal frames have a more favorable impact on consumer perceptions than round frames; this is contrary to left digit salience heuristic but is in line with anchoring and adjustment theory. The effect of just-below framing disappears both for deep discount levels and with sequential TPC discounts. This study has important managerial implications for the use of TPC as a promotional tool. The study also contributes to theory in multiple ways.